Multicultural Education In Indonesia: Characteristics And Urgency - Mappaenre, Andi; Ruswandi, Uus; Erihadiana, Mohamad; Nuraini, Yeni; Wiwaha, Rizzaldy Satria (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Indonesia is a multicultural country, both ethnic, religious, cultural, regional languages from Sabang to Merauke. On the one hand, this diversity is a gift for the Indonesian nation, but if it is not handled wisely, these differences have the potential to become a source of conflict for this nation. This study aims to discuss the urgency of multicultural education in Indonesia which focuses on its characteristics and application in the educational environment. The results of the study show that multicultural education is a must so that people do not only know about the diversity that exists but also have a practical and positive attitude towards diversity. Therefore, this multicultural education must be instilled as early as possible to the next generation of our nation in order to maintain the unity of this nation amidst the differences that exist.